DESIGN OF ARCHITECTURE ENTERPRISE MODEL INFORMATION SYSTEM ACADEMIC AND STUDENT ADMINISTRATION BUREAU USING TOGAF ADM - Karim, Arifin Andi Abd; iqbal, Iqbal (IJTB (International Journal of Technology And Business), 2019)
Information systems can help all types of businesses to improve the efficiency and effectiveness of business processes. These factors cause many organizations to implement information systems by only paying attention to momentary needs. So that the copy information overlaps and the system platform is different from one another, which is not in accordance with the mission and purpose of the application of information systems. One of the main causes of these different platforms is due to lack of planning and without thinking about the main key in the process of developing information system. In this study a case study of the design of an enterprise architecture model of the information system of the academic and student administration bureau (BAAK) was designed by applying the TOGAF ADM method. Stages - The stages of the Togaf ADM methodology are translated into enterprise architecture modeling namely architecture vision, business architecture, information system architecture and information technology. This research is limited to the main business processes based on mapping using the value chain and only reaches the Opportunities and Solution phase in TOGAF ADM with a sample of research at a private university in DKI Jakarta. The purpose of this research is to overcome the problem in the old system where some of the processing is found to be still managed manually. This research produces a blueprint of information system architecture in the form of application candidates for each sub-organization that is arranged based on the priority level of needs so that the implementation process is in accordance with the desired and does not interfere with the performance of the information system both running and being built. This research also serves as a reference for the foundation of the development of the SI architecture in the management of universities to be able to improve services. In this study, there can be seen a gap in business processes where in running a business at BAAK UNU has not used IT as its main requirement and also processing academic operational data still using standard applications such as Microsoft Office.